Intensive blood pressure lowering with nicardipine and outcomes after intracerebral hemorrhage: An individual participant data systematic review. Issue 5 (June 2022) - Toyoda, Kazunori; Yoshimura, Sohei; Fukuda-Doi, Mayumi; Qureshi, Adnan I; Martin, Renee' Hebert; Palesch, Yuko Y; Ihara, Masafumi; Suarez, Jose I; Okada, Yasushi; Hsu, Chung Y; Itabashi, Ryo; Wang, Yongjun; et al.
Background and aims: Nicardipine has strong, rapidly acting antihypertensive activity. The effects of acute systolic blood pressure levels achieved with intravenous nicardipine after onset of intracerebral hemorrhage on clinical outcomes were determined. Methods: A systematic review and individual participant data analysis of articles before 1 October 2020 identified on PubMed were performed (PROSPERO: CRD42020213857). Prospective studies involving hyperacute intracerebral hemorrhage adults treated with intravenous nicardipine whose outcome was assessed using the modified Rankin Scale were eligible. Outcomes included death or disability at 90 days, defined as the modified Rankin Scale score of 4–6, and hematoma expansion, defined as an increase ≥6 mL from baseline to 24-h computed tomography. Summary of review: Three studies met the eligibility criteria. For 1265 patients enrolled (age 62.6 ± 13.0 years, 484 women), death or disability occurred in 38.2% and hematoma expansion occurred in 17.4%. Mean hourly systolic blood pressure during the initial 24 h was positively associated with death or disability (adjusted odds ratio (aOR) 1.12, 95% confidence interval (CI) 1.00–1.26 per 10 mmHg) and hematoma expansion (1.16, 1.02–1.32). Mean hourly systolic blood pressure from 1 h to any timepoint during the initial 24 h was positively associated with death or disability. Later achievement of systolic blood pressure to ≤140 mmHg increased the risk of death or disability (aOR 1.02, 95% CI 1.00–1.05 per hour). Conclusions: Rapid lowering of systolic blood pressure by continuous administration of intravenous nicardipine during the initial 24 h in hyperacute intracerebral hemorrhage was associated with lower risks of hematoma expansion and 90-day death or disability without increasing serious adverse events.